Perancangan Online Virtual Gallery Dengan Memanfaatkan Teknologi HTML5 - Griko Stefan Tambahani; Michael Bezaleel Wenas; Ramos Somya (AITI, 2016)
Visual Communication Design is a Department in Information Technology Faculty. Annually, this study program conducts several exhibition events. However, there is a big problem in it that is no storage to store files of student works that usually are often damaged or vanished. By this research the researcher created an Online Virtual Gallery with the newest technology called HTML5 that use to store the files, such as: drawings, paintings, sketches, videos, games, etc. For the result, this research produced a virtual container that able to accommodate the works of DKV student, so that by this application expectantly could be help the student to store their exhibition files.